Polymorphisms in Genes Affecting Interferon-γ Production and Th1 T Cell Differentiation Are Associated With Progression to Chagas Disease Cardiomyopathy - Frade-Barros, Amanda Farage; Ianni, Barbara Maria; Cabantous, Sandrine; Pissetti, Cristina Wide; Saba, Bruno; Lin-Wang, Hui Tzu; Buck, Paula; Marin-Neto, José Antonio; Schmidt, André; Dias, Fabrício; Hirata, Mario Hiroyuki; Sampaio, Marcelo; et al. (Frontiers in Immunology, 2020)
Background Chagas disease, caused by the protozoan Trypanosoma cruzi, is endemic in Latin America. Thirty percent of infected individuals develop chronic Chagas cardiomyopathy (CCC), an inflammatory dilated cardiomyopathy that is the most important clinical consequence of T. cruzi infection, while the others remain asymptomatic (ASY). IFN- and IFN--producing Th1-type T cells are increased in peripheral blood and CCC myocardium as compared to ASY patients, while the Th1-antagonizing cytokine IL-10 is more expressed in ASY patients. Importantly IFN--producing Th1-type T cells are the most frequent cytokine-producing T cell subset in CCC myocardium, while expression of Th1-antagonizing cytokines IL-10 and IL-4 is unaltered. The control of IFN- production by Th1-type T cells may be a key event for progression towards CCC. A genetic component to disease progression was suggested by the familial aggregation of cases and the association of gene polymorphisms with CCC development. We here investigate the role of gene polymorphisms (SNPs) in several genes involved in the control of IFN-γ production and Th1 T cell differentiation in CCC development. Methods We studied a Brazilian population including 315 CCC cases and 118 ASY subjects. We assessed 35 Tag SNPs designed to represent all the genetic information contained in the IL12B, IL10, IFNG and IL4 genes. Results We found 4 IL12 SNPs (rs2546893, rs919766, rs1003199, rs11574790) and 2 IL10 SNPs (rs3024496 and rs18008) to be significantly associated with the ASY group. After multivariate analysis, two IL12B SNPs (rs2546893, rs919766) and one in IL10 (rs3024496) remained associated. No association was found for the studied IFNG or IL4 SNPs. Conclusions Our data show that novel polymorphisms affecting IL12B and IL10, but not IFNG or IL4 genes play a role in genetic susceptibility to CCC development. This might indicate that the increased Th1 differentiation and IFN-γ production associated with CCC is genetically controlled.